An Analysis Of Students’ Speaking Ability By Using Animated Movie At Eleventh Grade Of MAS Hubbulwathan - Joni Kurniawan (Unit Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Agama Islam Hubbulwathan, Duri, Indonesia, 2025)
This study deals with An analysis of students’ speaking ability by using animated movie at eleventh grade MAS Hubbulwathan. The purpose of this study was to focus on students’ speaking ability using animated movie at eleventh grade students at MAS Hubbulwathan. The researcher use descriptive, research design with quantitative approach The population of the research was the students at the eleventh grade MA Hubbulwathan which students consists of All students. The researcher took all students as samples 13 students. The students were selected by using saturated sampling. Techniques of collecting data was using a speaking test. The result of the data collecting and data analysis above, the researcher found the result showed the speaking ability by using animated movie at MA Hubbulwathan Duri 46.1% in high category. This research can be concluded that the students’ speaking ability at Eleventh grade students was generally categorized as High, where almost all students (84.61%) were able to demonstrate very good speaking performance based on the assessment instrument used.